1993
DOI: 10.1007/bf01970960
|View full text |Cite
|
Sign up to set email alerts
|

AsymptomaticNeisseria subflava biovarperflava bacteriuria in a child with obstructive uropathy

Abstract: A case of asymptomatic urinary tract infection with Neisseria subflava biovar perflava in a 10-year-old male patient with congenital structural abnormalities of the urinary bladder is presented. The organism was recovered from three catheter urine specimens collected over a seven-month period. A brief review of the role of saprophytic Neisseria species in infectious processes is presented and the likely source of this unusual urinary tract isolate is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Consistent with other studies of dogs, urine from both groups contained several genera previously reported as potential uropathogens, including Escherichia‐Shigella , Staphylococcus , Streptococcus , Corynebacterium , Pseudomonas , Neisseria , Sphingomonas , Actinomyces , Anaerococcus , Acinetobacter , Stenotrophomonas , Moraxella , and Roseomonas . 21 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 …”
Section: Resultsmentioning
confidence: 99%
“…Consistent with other studies of dogs, urine from both groups contained several genera previously reported as potential uropathogens, including Escherichia‐Shigella , Staphylococcus , Streptococcus , Corynebacterium , Pseudomonas , Neisseria , Sphingomonas , Actinomyces , Anaerococcus , Acinetobacter , Stenotrophomonas , Moraxella , and Roseomonas . 21 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 …”
Section: Resultsmentioning
confidence: 99%
“…Heart Endocarditis [183,184] Brain Meningitis [185][186][187] Blood Septicemia [145,186] Genitourinary tract Genital infections [148,180,188] Urinary infection [189] N. wadsworthii Skin Hand wound [172] Peritoneal fluid (Insufficient clinical data) [172] N. weaveri Blood Septicemia [190] Sputum Bronchiectasis [191] Peritoneum Peritonitis [192] Skin Wound [193,194] N. zoodegmatis Skin Ulceration [195] Table 1 Legend. Only exemplar clinical case reports of unusual infections with pathogenic and commensal Neisseria species are listed in the Table 1; characteristic (typical) infections with gonococcus (gonorrhea) and meningococcus (meningitis and septicemia) are not included.…”
Section: N Subflavamentioning
confidence: 99%